Social Structure, Habitat Use and Injuries of Indo-Pacific Bottlenose Dolphins (Tursiops aduncus) Reveal Isolated, Coastal, and Threatened Communities in the South Pacific - Bonneville, Claire Daisy; Derville, Solène; Luksenburg, Jolanda A.; Oremus, Marc; Garrigue, Claire (Frontiers in Marine Science, 2021)
Understanding population structure and habitat use of poorly known cetacean species is a first step toward scientifically informed management decisions. In the southern range of New Caledonia (South Pacific), a long-term dataset of Indo-Pacific bottlenose dolphins (Tursiops aduncus) encounters primarily during winter seasons 1997 to 2019 (473 group observations) was used to assess social structure, habitat use and potential threats. A total of 338 individuals were photographically identified, forming three distinct communities in the south-west lagoon, the south lagoon and the Isle of Pines. Mark-recapture histories revealed that the three communities were weakly connected and might be considered as independent management units. Suitable habitats were estimated with presence-only distribution models relative to topographic and seabed substrate predictors. Habitat suitability increased with proximity to coasts or reefs, at shallow depth, and over muddy bottom. These habitats had various levels of protection and were used by humans, mostly in the south-west lagoon. External injuries were interpreted to determine natural interactions and potential anthropogenic threats. The prevalence in injuries did not vary among the three areas. A substantial proportion of injuries related to propeller hits was reported, representing a total of 16.7% (34 of 204) of all injuries observed on dolphins. The three communities of Indo-Pacific bottlenose dolphins revealed in the southern part of New Caledonia are particularly vulnerable due to their insularity, their coastal habitat use and the low levels of connectivity found among them. In a context of increasing maritime traffic, fishing and recreational activities, this study provides a useful baseline to the urgent assessment of the conservation status of dolphins in New Caledonia.